RETRACTED: The effect of different variants of pig introductory crossing on the variability of blood protein metabolism - Garskaya Natal`ya; Tresnitskiy Sergey; Rudenko Andrey; Kochetkova Anastasiya; Savenkov Alexey (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001